Niels Wilhelm Gade’s Frühlings-Botschaft op. 35 and the Art of Musical Idyll - Lotzow, Alexander (Danish Yearbook of Musicology, 2018)
Drawing on Friedrich Schiller’s theory of idyll in poetry, the text asks for the relevance of idyll for the music of Niels W. Gade, exemplarily with regard to his choral-orchestral Frühlings-Botschaft op. 35 to a text by Emanuel Geibel. Contemporary reception, which explicitly classified the piece as ‘idyll’, praised it for several decades. Analysis of text and music suggests that this connectivity might be the consequence of the composition’s managing of creating a hypertrophy of aesthetic and structural layers, yet in an ulterior manner. With regard to Schiller’s utopia of Elysian idyll, Gade’s composition appears to come close to its ideal: by evoking tension without struggle, idyll without stagnancy. And it might be these kinds of assets that form not only a central trait of Gade’s choral-orchestral work but of his music in general.